2021
DOI: 10.3390/biomedicines9020181
|View full text |Cite
|
Sign up to set email alerts
|

Translational Research in FLASH Radiotherapy—From Radiobiological Mechanisms to In Vivo Results

Abstract: FLASH radiotherapy, or the administration of ultra-high dose rate radiotherapy, is a new radiation delivery method that aims to widen the therapeutic window in radiotherapy. Thus far, most in vitro and in vivo results show a real potential of FLASH to offer superior normal tissue sparing compared to conventionally delivered radiation. While there are several postulations behind the differential behaviour among normal and cancer cells under FLASH, the full spectra of radiobiological mechanisms are yet to be cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…Strikingly, FLASH irradiation (intra-pulse dose rates of ~10 6 -10 7 Gy/s with mean values in excess of 40-100 Gy/s) spares the surrounding healthy tissue while maintaining the same anti-tumor activity compared to conventional-dose-rate radiotherapy (~0.03 Gy/s) as shown in several animal model and pre-clinical studies (for reviews, see refs. [45][46][47][48][49]. Moreover, a recent first human patient treatment with FLASH-RT 50 has demonstrated that this technique may be transferable to the clinic.…”
Section: The Flash Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, FLASH irradiation (intra-pulse dose rates of ~10 6 -10 7 Gy/s with mean values in excess of 40-100 Gy/s) spares the surrounding healthy tissue while maintaining the same anti-tumor activity compared to conventional-dose-rate radiotherapy (~0.03 Gy/s) as shown in several animal model and pre-clinical studies (for reviews, see refs. [45][46][47][48][49]. Moreover, a recent first human patient treatment with FLASH-RT 50 has demonstrated that this technique may be transferable to the clinic.…”
Section: The Flash Effectmentioning
confidence: 99%
“…(70) FLASH-RT has become a hot topic in radiotherapy. The field has grown very quickly and several promising explanations of FLASH have been proposed (for a recent review, see, for example, ref 49…”
mentioning
confidence: 99%
“…The two main variants of SFRT with photons that have been studied and implemented include GRID radiotherapy (GRID RT) and lattice radiotherapy (LRT)—a 3D configuration of GRID, delivering spherical subvolumes of a high dose within the tumour. Ultra-high-dose-rate methods, including FLASH and microbeam radiotherapy, and LRT are beyond the scope of this review and can be found elsewhere in the literature [ 2 , 10 , 31 , 38 , 39 , 40 ].…”
Section: Preclinical and Clinical Evidence With Spatially Fractionate...mentioning
confidence: 99%
“…X-ray microbeams of average 100 KeV beam energy (spectrum 50–600 keV) are delivered at dose rates of 10 4 Gy/s up to 16 kGy/s [ 43 , 44 ]. Such dose rates trigger FLASH effects that confer additional biological benefits [ 45 ]. The biological FLASH effect was found to be reproducible when the whole dose of radiation is delivered in less than 200 milliseconds [ 46 ].…”
Section: Melanoma and Radiation Therapymentioning
confidence: 99%